2021
DOI: 10.7150/jca.63003
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression in Chinese Patients with Advanced Non-Small Cell Lung Cancer (NSCLC): A Multi-Center Retrospective Observational Study

Abstract: Objective: This study aimed to investigate the prevalence of tumor programmed death-ligand 1 (PD-L1) expression in Chinese patients with advanced Non-Small Cell Lung Cancer (NSCLC). Methods: Tumor tissues with histologically confirmed stage IIIB/IV NSCLC were retrospectively obtained from 10 centers in China. PD-L1 expression was determined using the PD-L1 IHC 22C3 pharmDx kit (Agilent, Santa Clara, CA, USA) and the samples were repetitively assayed with the PD-L1 IHC 22C3 Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
(68 reference statements)
2
9
0
Order By: Relevance
“…It is essential to realize that the variety of results and different prognostic impact of PD‐L1 in specific subgroups is influenced by the testing method itself (e.g., different antibodies and thresholds) and individual patient‐related characteristics, such as ethnicity or tumor histology. For instance, different proportions of PD‐L1‐positive tumors for distinct histological NSCLC subtypes have been reported 40–43 . In our study, high PD‐L1 TPS score carried both prognostic and predictive value in the ICI treated patients while in the whole cohort, including patients treated in curative settings, only the association between improved OS and CRP level of ≤10 was retained.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It is essential to realize that the variety of results and different prognostic impact of PD‐L1 in specific subgroups is influenced by the testing method itself (e.g., different antibodies and thresholds) and individual patient‐related characteristics, such as ethnicity or tumor histology. For instance, different proportions of PD‐L1‐positive tumors for distinct histological NSCLC subtypes have been reported 40–43 . In our study, high PD‐L1 TPS score carried both prognostic and predictive value in the ICI treated patients while in the whole cohort, including patients treated in curative settings, only the association between improved OS and CRP level of ≤10 was retained.…”
Section: Discussionmentioning
confidence: 50%
“…For instance, different proportions of PD-L1positive tumors for distinct histological NSCLC subtypes have been reported. [40][41][42][43] In our study, high PD-L1 TPS score carried both prognostic and predictive value in the ICI treated patients while in the whole cohort, including patients treated in curative settings, only the association between improved OS and CRP level of ≤10 was retained.…”
Section: Discussionmentioning
confidence: 63%
“…A study including 54 EGFR mutation samples identified only 9 samples with PD-L1 expression > 5% accounted for 9.3%. An analysis of PD-L1 expression levels in 871 Chinese NSCLC samples showed that patients with EGFR mutations had slightly lower PD-L1 positivity (43.8% and 49.8%, respectively), while higher PD-L1 expression (TPS ≥ 50%) was significantly lower (14.3% and 27.4%, respectively) compared with EGFR wild-type patients [18]. In addition, comprehensive analysis of PD-L1 and CD8 + TILs in 255 Chinese NSCLC samples showed that the proportion of PD-L1 + and CD8 + TILs double positive in TME was decreased, while the proportion of PD-L1and CD8 -TILs double negative was increased in EGFR mutation group compared with EGFR wild-type group patients (P < 0.01) [19].…”
Section: Discussionmentioning
confidence: 99%
“…All tissues were fixed with 10% formalin for at least 6 h. All samples were embedded in paraffin and then hematoxylin-eosin staining (HE) and IHC were conducted. All samples were analyzed on an automated stainer with 22C3 (PD-L1 test kits, DAKO/Agilent, USA) (26). At least two pathologists evaluated the slides to determine the scores of PD-L1-positive cells on TC and IC.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%